Analisis Soal dalam Buku Teks Matematika Kelas VIII Edisi Revisi 2017 Terbitan Kemendikbud Berdasarkan Dimensi Kognitif TIMSS 2019 - Nur Yuliany; Andi Halimah; Sabria; Munawarah; Sitti Zuhaerah Thalhah (Department of Mathematics Education, 2023)
This study aims to describe the first semester and second semester competency test questions contained in the revised 2017 edition of the junior high school mathematics textbook based on the cognitive dimensions of TIMSS 2019. This type of research is descriptive research using a qualitative approach. The data source in this study is the first semester competency test questions and the second semester competency test contained in the 2017 revised edition of the SMP/MTs grade VIII mathematics textbook written by Abdur Rahman As'ari, Mohammad Tohir, Erik Valentino, Zainul Imron and Ibnu Taufiq entitled